Le convenienze ed inconvenienze teatrali dramma giocoso in two acts - Donizetti, Gaetano 1797-1848 (Opus Arte, 2021)
Le convenienze ed inconvenienze teatrali ("The Conventions and Inconveniences of the Stage")--a joyful play on words in itself--more commonly known as Viva la mamma! is a two-act farce that shines an exaggerated spotlight on the behind-the-scenes working of a theatre and the rehearsal process with hilarious results
Bildformat: 16:9
Enthält Bonusmaterial: Cast gallery
Keywords: Operas; Feature films; Film; DVD-Video